UPAYA MENINGKATKAN GERAK DASAR LOKOMOTOR (KELINCAHAN DAN KECEPATAN) MELALUI PENDEKATAN BERMAIN (STUDI PADA SISWA KELAS X-4 SMAN 2 SIDOARJO) - SAFITRI SETYONINGRUM, RETNO (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The purpose of this research is to develope basic locomotor mantion (agility and speed) for 10th class using game approaching. Given the importance of the basic motion in the field of physical education sport and health as a basic study of motion exercise, it is considered very important to quickly resolve obstacles and barriers that exist. Various problems which led to a lack of basic motion (speed and agility). Ranging from the lack of activity of a given motion and a model given game lacks the element of agility and speed.This research uses classroom action research (CAR). Where the research is divided into two cycles. Each cycle consists of the PTK four stages, namely Plan, Action, Observation and Reflection. The results showed, was the approach taken playing time for each individual student's learning cycle seen no increase, to test the agility of 51% at the time of pre-test to 59% in cycle 1 and 73% in cycle 2. As for the test speed of 54% at the time of pre-test to 62% in cycle 1 and 70% in cycle 2. The conclusion of this study is the agility and speed of the students of class 10th four in senior high school 2 Sidoarjo results are improved and quite good. Keywords: basic motion locomotor (speed and agility), games, classroom action research